Molecular dynamics study on the influences of nanoparticle adhesion on interfacial thermal resistance and energy transport mechanism at a liquid-solid interface. (1st January 2013) - Matsumoto, T.; Miyanaga, S.; Shibahara, M.
The influences of nanoparticles adherent to a surface on the thermal resistance and the energy transport mechanism at a liquid-solid interface were investigated by non-equilibrium classical molecular dynamics simulations. The interaction potential parameters between the liquid molecules and the wall atoms and those between the liquid molecules and the nanoparticle atoms were changed for the parametric studies. The reduction of the interfacial thermal resistance caused by nanoparticle adhesion was observed in comparison with the flat surface when the interaction potential parameter between the liquid molecules and the nanoparticle atoms was relatively large and that between the liquid molecules and the surface atoms was relatively small. The simulation results showed that the interfacial liquid molecular density was strongly related to the variation of the interfacial thermal resistance as well as that of the energy transport mechanism.